In-vitro Cytotoxicity and In-silico Insights of the Multi-target Anticancer Candidates from Haplophyllum tuberculatum - Mosab Yahya Al-Nour; Ahmed H Arbab; Mohammad Khalid Parvez; Arwa Y Mohamed; Mohammed S Al-Dosari (Borneo Journal of Pharmacy, 2021)
This study aimed to investigate the anticancer activity of Haplophyllum tuberculatum(Forsk.) aerial parts ethanol extract and fractions and reveal the potential anticancer targets, binding modes, pharmacokinetics, and toxicity properties of its phytoconstituents. MTT assay was used to investigate the anticancer activity. TargetNet, ChemProt version 2.0, and CLC-Pred web servers were used for virtual screening, and Cresset Flare software was used for molecular docking with the 26 predicted targets. Moreover, pkCSM, swiss ADME, and eMolTox web servers were used to predict pharmacokinetics and safety. Ethanolic extracts of H. tuberculatum on HepG2 and HeLa cell lines showed promising activities with IC50 values 54.12 and 48.1 µg/mL, respectively. Further, ethyl acetate fraction showed the highest cytotoxicity on HepG2 and HeLa cell lines with IC50 values 41.7 and 52.31 µg/mL. Of 70 compounds screened virtually, polygamain, justicidin A, justicidin B, haplotubine, kusunokinin, and flindersine were predicted as safe anticancer drugs candidates. They showed the highest binding scores with targets involved in cell growth, proliferation, survival, migration, tumor suppression, induction of apoptosis, metastasis, and drug resistance. Our findings revealed the potency of H. tuberculatum as a source of anticancer candidates that further studies should support.